2020
DOI: 10.3389/fnbeh.2020.00028
|View full text |Cite
|
Sign up to set email alerts
|

Trait Anxiety Attenuates Response Inhibition: Evidence From an ERP Study Using the Go/NoGo Task

Abstract: Neuropsychology and cognitive neuroscience have shown that anxious individuals have deficits in response inhibition. However, existing knowledge about the influence of trait anxiety on response inhibition is still inconsistent. The aim of this study was to investigate response inhibition between groups with high trait anxiety (HTA) and low trait anxiety (LTA). Here, we used event-related potential (ERP) indexes as biomarkers to examine the effect of trait anxiety on response inhibition using the Go/NoGo task. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Our first finding revealed no significant difference in the SSRT between the HTA and LTA groups, suggesting that trait anxiety does not have a substantial effect on behavioral competence of response inhibition. However, other studies that have applied the go/no-go (Xia et al, 2020) or the Stroop task (Basten et al, 2011) revealed behavioral deficits of inhibitory function in individuals with HTA compared to those with LTA. It should be noted that the p-value (p = 0.08, two-tailed) in the present study was very close to significance given a sample size with 20 subjects in each group.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our first finding revealed no significant difference in the SSRT between the HTA and LTA groups, suggesting that trait anxiety does not have a substantial effect on behavioral competence of response inhibition. However, other studies that have applied the go/no-go (Xia et al, 2020) or the Stroop task (Basten et al, 2011) revealed behavioral deficits of inhibitory function in individuals with HTA compared to those with LTA. It should be noted that the p-value (p = 0.08, two-tailed) in the present study was very close to significance given a sample size with 20 subjects in each group.…”
Section: Discussionmentioning
confidence: 91%
“…Abnormalities in inhibitory control and error monitoring have been frequently reported in clinical forms of anxiety (Eysenck et al, 2007;Moser et al, 2013). However, the effects of trait anxiety, a subclinical form of anxiety, on inhibitory control and error monitoring remain inconclusive (Moser et al, 2012;Saunders and Inzlicht, 2020;Xia et al, 2020). Therefore, this study aimed to investigate whether and to what extent trait anxiety modulates inhibitory control, error processing, and adaptive behavior after making a mistake.…”
Section: Introductionmentioning
confidence: 99%
“…and anxiety(Righi, Mecacci, & Viggiano, 2009;Xia, Mo, Wang, Zhang, & Zhang, 2020). The findings collectively suggested a link between psychopathology and altered neural processing underlying inhibitory control.…”
mentioning
confidence: 79%
“…It requires the subject to respond between performing or inhibiting the motor response. The stopping task requires the inhibition of a motor response triggered by a “stop” signal shortly after the start signal, thus converting the start response posterior to a forbidden response, involving the withdrawal of a response already triggered by the Go signal [ 14 ]. Other experiments have shown that various regions of the brain are related to behavioral execution and behavioral inhibition in the Go/No go task, including the orbital gyrus, inferior frontal gyrus, medial frontal lobe, temporal lobe, parietal cortex [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%